Estudo da assimetria da fossa mandibular, em crânios secos de crianças pelo método radiográfico - Rocha, João Carlos da [UNESP] (1999)
The Temporomandibular Joint is a noble structure of the complex mandibular, a lot of research was conducted on the to signs and symptoms of the alterations that attack those structures. ln spite of the high incidence of the DTM in children, there's little knowledge about it, wich makes difficult the treatment Desorders Craniomandibulares (DCM) or Desorders Temporomandibulars (DTM). The Temporomandibular Joint is composed basically by three elements: bones, muscles and disk, in relation to bony part, we have the fossae mandibular that is part of the temporary bone and wich houses the condyle mandibular, accomplishing the articulation among the cranium and the jaw (it leaves piece of furniture of the articulation). Our intention in that work was of verifying a possible asymmetry of the fossae mandibular on the left side and of the right side in relation to two straight line: a straight line that coincided with the plane medium sagittal and another perpendicular straight line to the plan medium sagittal. Analyzing, the fossae mandibular in 91 dry craniums of children, with age varying between four months of life intrauterina and five years, in x-rays in that the incidence was cranium-flow, we could end that: in spite of we find statistical significance in relation to that asymmetry, clinic cannot affirm that interferences on occlusion exists for that asymmetry